DERMATOLOGICAL MORBIDITY IN PATIENTS WITH PRIMARY PSYCHIATRIC CONDITIONS - Maqsood, Niaz; Niaz, Naima; Hassan, Summaira (Journal of Pakistan Psychiatric Society, 2021)
OBJECTIVE: To find the frequency and type of dermatological disease in patients with primary psychiatric conditions. METHODS: This cross-sectional study was conducted on 200 psychiatric patients admitted in psychiatry department of Bahawal Victoria Hospital, Bahawalpur. RESULTS: In this study conducted on 200 psychiatric patients, 82% had dermatological disease and out of them 72% had infectious dermatological diseases CONCLUSION: Dermatological diseases particularly infectious dermatological diseases were prevalent among patients with psychiatric disorders.